Tesoros turísticos de Colombia: Análisis comparativo (benchmarking) de la oferta turística de Santa Marta frente a las ciudades colombianas de Cartagena, Medellín y Bogotá, durante el año 2022 (2023)
The aim of this research is to carry out a comparative analysis of the tourist offer of Santa Marta in comparison to Cartagena, Medellin, and Bogota during the year 2022, from a benchmarking approach. To achieve this, an exhaustive study of the strengths, opportunities, weaknesses, and threats of each tourist destination will be carried out, taking into account the social, cultural, economic, and environmental aspects. Furthermore, an analysis of the tourist supply and demand, tourist competitiveness, implemented strategies and policies, and the impact of tourism in each destination will be conducted. Lastly, the concept of regenerative tourism and its possible application in the selected tourist destinations will be addressed. Based on the gathered information, conclusions and recommendations will be presented to improve the tourist offer in each destination and increase their competitiveness in the national and international tourism market. The methodology to be followed will be a descriptive and comparative research through existing literature, that is, a bibliographic review. It is important to mention that this research seeks to contribute to the knowledge and analysis of the tourism sector in Colombia regarding its current situation, particularly of the city of Santa Marta compared to the selected tourist destinations. Additionally, it is expected that the presented conclusions and recommendations can be useful for the actors in the tourism sector, such as companies, local governments, tourism organizations, and local communities. It is also hoped that this work can serve as a basis for future research in the area of tourism and its impact on tourist destinations.